Association of nutritional status with dietary and behavioural patterns among adolescents - Elizabeth, Kandathil Eapen; Ashwin, David Ashok; Jothydev, Kesavadev (International Journal of Contemporary Pediatrics, 2020)
Background: Changing trends in dietary habits, behavioral patterns, and prevalence of overweight/obesity among adolescents is of great concern. Methods: 6469 school children from five districts of Kerala, India were enrolled. Dietary habits and behavioral patterns were collected using a pretested questionnaire. Anthropometric measurements were recorded and compared with regional Indian Academy Pediatrics (IAP) reference charts. Data was computed and analyzed. Results: Mean age: Boys 14.51±0.93, Girls 14.42±1.04 years. Male: Female ratio 0.92:1. Practices like missing breakfast, non-compliance to weekly Iron Folic Acid supplementation and not taking exercise >2 hours/week were more in girls. Increased consumption of junk food, screen time >2 hours/week and not sharing life events with parents were more in boys. Mean anthropometric parameters were <50th percentile of reference charts. 6.1% had low BMI (boys, 4.2% vs. girls,7.6%,), 12.3% were overweight (boys, 14.9% vs. girls,10.2%) and 4.4% had obesity (boys, 4.7% vs. girls, 4.2%). Mean anthropometric parameters were higher in more urbanized districts. Daily consumption of junk food showed significant association with obesity and exercise >2 hours/week with normal BMI. Conclusions: Dietary and behavioral patterns and prevalence of overweight/obesity showed variability with respect to gender and region of residence. 12% were overweight and 4% had obesity. Daily consumption of junk food showed significant association with overweight/obesity and daily exercise >2 hours/week with normal BMI. Health education addressing behavioral change is recommended for better health.